“Hipertensión gestacional en embarazada de 36 semanas de gestación” - José Gilberto, Ramírez Carbo (2019)
Hypertensive disorders of pregnancy are among the most important complications that occur in pregnancy . If not treated in time, they lead to high morbidity and mortality for both the mother and the fetus. An early evaluation would be the best for each situation in the most conscious, way considering the adverse effect of the drugs that are used in the mother and its impact on the fetus. Arterial Hypertesion that occurs after twenty weeks of gestation and recovers after delivery correspond to the second group , may be gestational Hypertesion or transitory , when the Arterial Hypertesion is only the clinical sign, or preeclampsia, a multisystem syndrome in which the most frequent manifestation is proteinuria Arterial Hypertesion its diagnosis should be considered when a target of any white organ. Without Proteinuria, Eclampsia defines the picture of seizuresin a patient with preeclampsia. A pregnant woman with Chronic arterial Hypertesion can manifest a preeclampsia over-aggregated , being these the ranks of worse perinatal maternal prognosis.